2015
DOI: 10.1111/jpet.12118
|View full text |Cite
|
Sign up to set email alerts
|

Tax Havens, Growth, and Welfare

Abstract: This paper develops an endogenous growth model featuring tax havens, and uses it to examine how the existence of tax havens affects the economic growth rate and social welfare in high-tax countries. We show that the presence of tax havens generates two conflicting channels in determining the growth effect. First, the public investment effect states that tax havens may erode tax revenues and in turn decrease the government's infrastructure expenditure, thereby reducing growth. Second, the tax planning effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Picard and Pieretti (2011) aimed at observing the effect of pressure policies such as blacklisting and sanctions on offshore financial centres (OFCs hereafter) and their ability to ensure compliance with AML regulations. Instead of analysing the desirability or harm of tax havens (Alstadsaeter et al, 2018;Christensen, 2012;Chu et al, 2015), Picard and Pieretti focused on the incentives for offshore governments and banks to comply with AML regulations. They found that offshore banks would comply under pressure policies provided the pressure had potential to harm the reputation of investors.…”
Section: Effect Of Money Laundering On Other Fields and The Economymentioning
confidence: 99%
“…Picard and Pieretti (2011) aimed at observing the effect of pressure policies such as blacklisting and sanctions on offshore financial centres (OFCs hereafter) and their ability to ensure compliance with AML regulations. Instead of analysing the desirability or harm of tax havens (Alstadsaeter et al, 2018;Christensen, 2012;Chu et al, 2015), Picard and Pieretti focused on the incentives for offshore governments and banks to comply with AML regulations. They found that offshore banks would comply under pressure policies provided the pressure had potential to harm the reputation of investors.…”
Section: Effect Of Money Laundering On Other Fields and The Economymentioning
confidence: 99%
“…While international tax transparency can function as a global public good, such coordination can also have drawbacks. First, coordination is not always growth or welfare-enhancing as the effects on capital accumulation and investment can be ambiguous (Chu et al, 2014). The institutional set-up matters and so does whether countries are capital exporting or importing (Bacchetta and Espinoza, 1995).…”
Section: The Importance Of Tax Coordinationmentioning
confidence: 99%